The emergence of visual responses in the developing retinotectal system in vivo - Van Rheede, J (2013)
Patterned neuronal activity driven by the sensory environment plays a key role in the development of precise synaptic connectivity in the brain. It is well established that the action potentials (‘spikes’) generated by individual neurons are crucial to this developmental process. A neuron’s spiking activity is jointly determined by its synaptic inputs and its intrinsic excitability. It is therefore important to ask how a neuron develops these attributes, and whether the emergence of spiking might itself be governed by activity-dependent processes. In this thesis, I address these questions in the retinotectal system of Xenopus laevis. First, I investigate the extent to which visuospatial information is available to the developing retinotectal system. I show that the eyes of developing Xenopus larvae are hyperopic at the onset of vision, but rapidly grow towards correct vision. Despite its imperfect optics, the Xenopus eye is able to generate spatially restricted activity on the retina, which is evident in the spatial structure of the receptive fields (RFs) of tectal neurons. Using a novel method to map the visually driven spiking output and synaptic inputs of the same tectal neuron in vivo, I show that neuronal spiking activity closely follows the spatiotemporal profile of glutamatergic inputs. Next, I characterise a population of neurons in the developing optic tectum that does not fire action potentials, despite receiving visually evoked glutamatergic and γ-aminobutyric acid (GABA)ergic synaptic inputs. A comparison of visually spiking and visually non-spiking neurons reveals that the principal reason these neurons are ‘silent’ is that they lack sufficient glutamatergic synaptic excitation. In the final section of the thesis, I investigate whether visually driven activity can play a role in the ‘unsilencing’ of these silent neurons. I show that non-spiking tectal neurons can be rapidly converted into spiking neurons through a visual conditioning protocol. This conversion is associated with a selective increase in glutamatergic input and implicates a novel, spike-independent form of synaptic potentiation. I provide evidence that this novel plasticity process is mediated by GABAergic inputs that are depolarising during early development, and can act in synergy with N-methyl-D-aspartate receptors (NMDARs) to strengthen immature glutamatergic synapses. Consistent with this, preventing the depolarising effects of GABA or blocking NMDARs abolished the activity-dependent unsilencing of tectal neurons. These results therefore support a model in which GABAergic and glutamatergic transmitter systems function synergistically to enable a neuron to recruit the synaptic excitation it needs to develop sensory-driven spiking activity. This represents a transition with important consequences for both the functional output and the activity-dependent development of a neuron.